GROWTH OF POTATO SEEDS (Solanum tuberesum L.) ON MS MEDIA SUBSTITUTED WITH COCONUT WATER - Edy F. Lengkong; hizkia mantiri; Arthur G. Pinaria (Sam Ratulangi University, 2023)
The tissue culture technique can be the best method of choice because it is fast in propagation and has a relatively short time. This research was conducted using a completely randomized design, with 4 treatments, namely: P0. MS Media 100%, P1. MS Media 90% + 10% Coconut Water, P2. MS Media 80% + 20 Coconut Water, P3. MS Media 70% + 30% Coconut Water. Each treatment was repeated 10 times to obtain 40 experimental units and in each experimental unit/bottle, there were 2 shoot explants. The results of the study that the substitution of Coconut Water in MS Media had a significant effect on plant height parameters but had no significant effect on parameters of number of leaves, number of roots, number of branches, and dry weight of potato plantlets. The best use of coconut water as a substitute for MS media for the growth of potato plantlets is at a concentration of 30%. because it did not differ from the control (100% MS media), especially the parameters of the number of leaves, number of roots, number of branches, and dry tissue of potato plantlets. Keywords: Potato Seeds, MS Media, Coconut water Abstrak Teknik kultur jaringan dapat menjadi pilihan metode terbaik karena cepat dalam perbanyakannya dan memiliki waktu yang relatif singkat. Penelitian ini dilakukan dengan menggunakan rancangan acak lengkap, dengan 4 perlakuan yaitu: P0. MS Media 100%, P1. MS Media 90% + 10% Air Kelapa, P2. MS Media 80% + 20 Air Kelapa, P3. MS Media 70% + 30% Air Kelapa. Setiap perlakuan diulang sebanyak 10 kali sehingga diperoleh 40 satuan percobaan dan pada setiap satuan percobaan/botol terdapat 2 eksplan pucuk. Hasil penelitian bahwa substitusi Air Kelapa pada Media MS berpengaruh nyata terhadap parameter tinggi tanaman namun tidak berpengaruh nyata terhadap parameter jumlah daun, jumlah akar, jumlah cabang, dan berat kering planlet kentang. Pemanfaatan air kelapa sebagai pengganti media MS untuk pertumbuhan planlet kentang yang terbaik adalah pada konsentrasi 30%. karena tidak berbeda dengan kontrol (media 100% MS) terutama pada parameter jumlah daun, jumlah akar, jumlah cabang, dan jaringan kering planlet kentang. Kata Kunci : Benih Kentang, MS Media, Air Kelapa